Linear Decision Rules for Economic Stabilization and Growth - Holt, Charles C. (Quarterly Journal of Economics, 1962)
I. Introduction, 20. — II. A linear decision rule, 22; decision rule for static uncertainty, 23; decision rule for dynamic uncertainty, 25; plans, 28. — III. Simulation tests of the dynamic decision rule under uncertainty, 29; the policy of inaction, 30; decision rule stabilization with poor forecasts, 32; decision rule stabilization with perfect forecasts, 33; performance comparisons, 34; errors in estimating the economic relations and the welfare function, 38. — IV. Economic growth, 39. — V. Stabilization of an inherently unstable economy, 42. — VI. In conclusion, 43.